Optimal reactive power dispatch using backtracking search algorithm - Shaheen, Abdullah M.; El-Sehiemy, Ragab A.; Farrag, Sobhy M. (Australian journal of electrical & electronics engineering, 2016)
Optimal reactive power dispatch (ORPD) problem has a mounting effectuation on secure and economical operation of electrical power systems. It is well-known as a non-linear, multimodal and mixed-variable problem which has been solved using various computation intelligence-based techniques in the last decades. In this paper, as a new approach, backtracking search algorithm (BSA) is applied to solve the ORPD problem to minimise the power losses and/or improve the voltage profile under control and dependent variable constraints. The BSA is a new evolutionary algorithm for solving real-valued numerical optimisation problems. It has a simple structure and single control parameter. It memorises a population from a randomly chosen previous generation for use in generating the search-direction matrix. This grants BSA the advantage of experiences gained from previous generations to generate the offsprings. The proposed BSA is applied to the IEEE standard 30-bus system, and a real power system at West Delta Network as a part of the Unified Egyptian Network. Simulation results show the capability of the proposed BSA for solving the ORPD problem.